Facilitating cooperation in transdisciplinary research and evaluating its role in SenseMaker® for a developing world context - Pylipow, Joshua Michael (Stellenbosch : Stellenbosch University, 2018)
Thesis (MPhil)--Stellenbosch University, 2018.